Global transcriptional changes caused by an EDMD mutation correlate to tissue specific disease phenotypes in C. elegans. (2nd January 2017) - Zuela, Noam; Dorfman, Jehudith; Gruenbaum, Yosef
Abstract: There are numerous heritable diseases associated with mutations in the LMNA gene. Most of these laminopathic diseases, including several muscular dystrophies, are autosomal dominant and have tissue-specific phenotypes. Our previous studies have shown that the globally expressed Emery-Dreifuss muscular dystrophy (EDMD)-linked lamin mutation, L535P, disrupts nuclear mechanical response specifically in muscle nuclei of C. elegans leading to atrophy of the body muscle cells and to reduced motility. Here we used RNA sequencing to analyze the global changes in gene expression caused by the L535P EDMD lamin mutation in order to gain better understanding of disease mechanisms and the correlation between transcription and phenotype. Our results show changes in key genes and biological pathways that can help explain the muscle specific phenotypes. In addition, the differential gene expression between wild-type and L535P mutant animals suggests that the pharynx function in the L535P mutant animals is affected by this lamin mutation. Moreover, these transcriptional changes were then correlated with reduced pharynx activity and abnormal pharynx muscle structure. Understanding disease mechanisms will potentially lead to new therapeutic approaches toward curing EDMD.